2008
DOI: 10.1097/aud.0b013e31818005bd
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit Obtained from Visually Displayed Text from an Automatic Speech Recognizer During Listening to Speech Presented in Noise

Abstract: The present study indicates that speech comprehension improves considerably by textual ASR output with moderate accuracies. The study shows that this improvement depends on the readability of the ASR output. Word output has better accuracy and readability than phone output. Listeners are therefore better able to use the ASR word output than phone output to improve speech comprehension. The ability of older listeners and listeners with hearing impairments to use ASR output in speech comprehension requires furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…Forevaluating such an audiovisual combination it can be researched howthe SRT (being the SNR levelofspeech in noise as measured at the 50% intelligibility threshold)w ill improve when simultaneously presenting the (imperfectly)t ranscripted speech as text on adisplay. Figure 10 shows the mean improvement in SRTf or normal hearing persons for the standard Dutch sentences when adding transcripted speech from aspeech recognizer at 37%, 55% and 74% accuracyand for delays of zero, 2, 4or6seconds [38]. It can be seen that the required SNR for 50% understanding improvesby0.5 to 3.5 dB.…”
Section: Automatic Speech Recognition To Assist Speech Understandingmentioning
confidence: 99%
See 1 more Smart Citation
“…Forevaluating such an audiovisual combination it can be researched howthe SRT (being the SNR levelofspeech in noise as measured at the 50% intelligibility threshold)w ill improve when simultaneously presenting the (imperfectly)t ranscripted speech as text on adisplay. Figure 10 shows the mean improvement in SRTf or normal hearing persons for the standard Dutch sentences when adding transcripted speech from aspeech recognizer at 37%, 55% and 74% accuracyand for delays of zero, 2, 4or6seconds [38]. It can be seen that the required SNR for 50% understanding improvesby0.5 to 3.5 dB.…”
Section: Automatic Speech Recognition To Assist Speech Understandingmentioning
confidence: 99%
“…Such aspeech to text transcription system can be offered as an online service for (web-)t elephony, in which ar emote Figure 10. Improvement of SRTb yp resenting transcripted speech from ASR at 3l evels of accuracya nd for 0, 2, 4a nd 6 secs of processing delay (from [38]). server provides the calculation intensive ASR processing.…”
Section: Automatic Speech Recognition To Assist Speech Understandingmentioning
confidence: 99%
“…There is much evidence that sensory processing of speech in auditory cortex can be modulated by higher order processing, such as syntactic or semantic analysis (Miller and Isard 1963; Kalikow et al 1977; Peelle et al 2012; Peelle 2013), speaker familiarity (Johnsrude et al 2013) or linguistic expectations set up by visual cues (Jacoby et al 1988; Zekveld et al 2008; Sohoglu et al 2012; for review: Peelle et al 2010). Sohoglu and colleagues (using EEG and MEG) showed that a visual cue, which provides prior knowledge of the speech content, increases the perceived speech clarity in a similar manner as altering the physical parameters of the stimulus.…”
Section: 2 Effects Of Linguistic Processing On Sensory Responsesmentioning
confidence: 99%
“…However, it is not always possible to see the talker, and visual facial information alone is ambiguous. Orthographic text may serve as an alternate source of visual speech information to supplement aided speech in adverse listening conditions, both in young and in older adults (Zekveld et al 2008, 2009). …”
Section: Introductionmentioning
confidence: 99%